2012
DOI: 10.1161/circoutcomes.111.962837
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Versus Femoral Artery Access Options in Coronary Angiogram Procedures

Abstract: Background— Vascular access options in coronary angiography can be considered a preference-sensitive decision, where the benefits/risks have different levels of significance, depending on the individual patient. For preference-sensitive healthcare options, patient decision aids (PtDA) significantly improve the process of decision-making. The purpose of this trial was to evaluate the effectiveness of an evidence-based PtDA compared with usual care in patients eligible for radial and femoral artery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 17 publications
0
43
1
Order By: Relevance
“…Twenty-six of the 61 studies involved a patient decision aid [16,18,20,22,25,32,33,[47][48][49][50][51][52][53]56,[58][59][60][61]64,66,68,[72][73][74][75]. Four additional studies reported using education materials such as educational sessions or pamphlets but did not refer to them as decision aids [17,43,63,70].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…Twenty-six of the 61 studies involved a patient decision aid [16,18,20,22,25,32,33,[47][48][49][50][51][52][53]56,[58][59][60][61]64,66,68,[72][73][74][75]. Four additional studies reported using education materials such as educational sessions or pamphlets but did not refer to them as decision aids [17,43,63,70].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…The study found that the decision aid resulted in a significant reduction in decisional conflict (unadjusted results), an increase in knowledge, and an increase in percentage of patients who made an informed, values-congruent choice. 6 There was no difference in the rates of procedures, nor in the success or safety of the procedures between the two groups, although the study was not powered to detect such differences.…”
Section: Articles See P 251 and 260mentioning
confidence: 94%
“…Further, the decision aid arm had significantly fewer admissions to the observation unit (58% versus 77%) compared with the control group, and there was no difference in 30-day cardiac adverse events. 5 The second study, a randomized, controlled trial by Schwalm and colleagues, 6 evaluated a patient decision aid that focused on femoral versus radial artery access for coronary angiography. The decision aid was a 3-page booklet that patients reviewed immediately before the catheterization.…”
Section: Articles See P 251 and 260mentioning
confidence: 99%
“…Randomized, controlled trials of DAs for coronary artery disease treatment, statin use, anticoagulation for atrial fibrillation, heart failure self-management, vascular access for cardiac catheterization, acute low-risk chest pain, and coronary artery disease prevention have shown that use of such DAs improves the decision-making process by increasing knowledge, improving risk communication, decreasing decisional conflict, increasing participation in care, and increasing value congruence. [43][44][45][46][47][48] The effect of DAs on such outcomes as self-efficacy and medication adherence has not yet been definitively established.…”
Section: Efficacy Of Das For Decision Support For Cardiovascular Disementioning
confidence: 99%